Positive relationship between wood size and basidiocarp production of polypore fungi in Alnus acuminata forest - Urcelay, Roberto Carlos (2009)
Polypores play a major role in wood decomposition. Based on presence/absence of basidiocarps, it has been shown that richness of polypores in forests is strongly affected by the size of logs. However, no study has addressed the relationship between the log size and basidiocarp production. Here, we examined the relationship between log diameter and number of basidiocarps and volume of the fructification (as surrogate of biomass) of the polypore community in Andean Alder forests from Northwest Argentina. We found a positive relationship between log diameter and basidiocarp production in the whole community analysis (fructifications of all species). This pattern was also followed by dominant species (Bjerkandera adusta, Trametes cubensis and T. versicolor) analyzed individually. The relationship was generally higher for volume of fructification than for number of basidiocarps. Through these effects on basidiocarp production, higher log diameter could promote higher sexual spore production and dispersal hence a higher genetic variability and viable populations of wood-decay species.